PENGARUH GREEN ACCOUNTING, KINERJA LINGKUNGAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERTAMBANGAN DI INDONESIA PERIODE 2021-2025 - Sherin Oktaviani; Elyanti Rosmanidar; Muthmainnah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of green accounting, environmental performance, and profitability on firm value in mining companies listed on the Indonesia Stock Exchange during the 2021–2025 period. This research uses a quantitative approach with panel data regression analysis method. The population of this study consists of mining companies listed on the Indonesia Stock Exchange, while the sample was determined using purposive sampling technique, resulting in 10 companies observed over five years. The research data are secondary data obtained from annual reports, sustainability reports, and PROPER data issued by the Ministry of Environment and Forestry. Data analysis was conducted using EViews 12 software. The results indicate that green accounting has a positive and significant effect on firm value. This finding suggests that the disclosure of environmental costs and corporate environmental responsibility can increase investor confidence. Environmental performance measured using PROPER ratings also has a positive and significant effect on firm value. The better the company’s environmental management, the higher the market valuation of the company. Profitability proxied by Net Profit Margin (NPM) also has a positive and significant effect on firm value. A high level of profitability reflects the company’s ability to generate profits, thereby increasing its attractiveness to investors. Simultaneously, green accounting, environmental performance, and profitability significantly affect firm value. This study is expected to serve as a reference for companies in improving the implementation of environmental accounting and sustainable environmental management in order to enhance firm value and attract investors.